REPRESENTASI GAY DALAM FILM MOONLIGHT - Elisa Gunawati; Feri Ferdinan Alamsyah; Roni Jayawinangun (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
Gay or homosexuality is a variation of developed sexual orientation in society. The purpose of this research is to know the gay representation in Moonlight film and to know semiotic analysis of Charles Sanders Peirce in Moonlight film. Research design and research method used in this thesis is qualitative research method of Semiotics Charles Sanders Peirce and Queer Theory. The analysis of each scene has been selected as many as six scenes showing gay signs and then analyzing using Peirce model that is relation of Sign / Interpretant, Object, and Interpretant which each consist of trichotomy based on the sign that is qualisign, sinsign, and legisign, based on the object ie icon, index, and symbol, and based on interpretantnya rheme, dicisign, and argument. After observing and analyzing the scene / scene in the movie "Moonlight", researchers found the presence of gay signs in the film as a sense of curiosity Chiron against gays and homos, Chiron who seek with his identity, sexual behavior such as kissing and Kevin's masturbation against Chiron, anxiety and longing for someone, dreaming or fantasizing until ejaculation, meeting the person and embracing him, and behaving differently to his peers.Keywords: Representation, Gay, Semiotics, Moonlight